Larvas de Geometridae (Lepidoptera) e seus parasitoides em sub-bosque nativo na Universidade Federal de São Carlos, Campus São Carlos, Estado de São Paulo - Geraldo, Mariana (2011)
Geometridae larvae and their parasitoids were surveyed in a understory at Universidade Federal de São Carlos, Campus São Carlos, SP. Larvae were colected among April 2009 to April 2010, with an entomological umbrella in 18 native species plants. It obtained 863 larvae including 46 species and 24 genera belong to majority the Ennominae. The Larentiinae and Sterrhinae subfamilies were also represented for Eois and Cyclophora, respectively. The Ennominae genus obtained were: Certima, Glena, Herbita, Hymenomima, Iridopsis, Ischnopteris, Isochromodes, Lomographa, Macaria, Melanolophia, Microgonia, Microxydia, Nematocampa, Oxydia, Patalene, Pero, Phyllodonta, Physocleora, Prochoerodes, Sabulodes, Thyrinteina and Trotopera. Macaria rigidata was the more abundant species which represented 31%. It recorded 174 parasitized larvae from which 337 parasitoids emerged. They are distributed among Braconidae, Ichneumonidae, Eulophidae (Hymenoptera) and Diptera, with Hymenoptera predominance. The obtained parasitoids were: Diolcogaster, Protapanteles, Glyptapanteles, Aleiodes, (Braconidae), Casinaria, Charops, Cryptophion, Diradops, Dusona, Jomine, Neotheronia, Podogaster, Polycyrtus, Mesochorinae (Ichneumonidae), Euplectrus (Eulophidae) and Tachinidae (Diptera). It recorded new parasitoids species of the genus: Diradops, Jomine and Neotheronia (Hymenoptera, Ichneumonidae). Geometridae larvae were present throughout the collection period and had increased occurrence at the end of rainy season.